Advancing Research and Training on Ageing, Place and Home - Papp, Katalin (Magyar Gerontológia, 2023)
HOMeAGE Doctoral Network Older Adult Reference Group MeetingHorizon Europe (HORIZON) Marie Skłodowska-Curie Actions Doctoral NetworksHOMeAGE (101073506)